Pengolahan Produk Inovasi Bernilai Tambah dari Kearifan Lokal berupa Wadi Ikan Patin (Pangasius sp.) dengan Penambahan Wijen pada Poklahsar Tampung Parei Kota Palangka Raya - Petrus Senas; Evnaweri Evnaweri; Tyas Wara Sulistyaningrum (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
This activity was carried out at Poklahsar Tampung Parei Jalan Tingang VIIB/Bukit Pengharapan No.2 Palangka Village, Jekan Raya Sub-District, Palangka Raya City on Tuesday, September 10, 2019. The purpose of this activity was to transfer knowledge and technology for processing value-added fish products for added value. Poklahsar Tampung Pare utilizes local wisdom so that it can produce new variant products. The open mindset of participants of the Fisheries Product Technology Study Program at Palangkaraya University to learn entrepreneurship with the skills they have to prosper their lives going forward. The activity was carried out by giving material to the Community Service Team in discussions with fish processing products entrepreneurs and demonstration of the manufacture of new products by adding sesame powder to processed products of wadi patin. Value-added processed fish products from local wisdom have advantages over other products. Besides being a product with a variety of new flavors, it can also increase consumer interest in buying to increase income and improve the welfare of the community, especially fisheries processing.